2014
DOI: 10.3109/01480545.2014.933348
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism disturbances contribute to insulin resistance and decrease insulin sensitivity by malathion exposure in Wistar rat

Abstract: Several studies showed that organophosphorus pesticides disturb glucose homeostasis and can increase incidence of metabolic disorders and diabetes via insulin resistance. The current study investigates the influence of malathion on glucose metabolism regulation, in vivo, during subchronic exposure. Malathion was administered orally (200 mg/kg), once a day for 28 consecutive days. Plasma glucose, insulin and Glycated hemoglobin levels were significantly increased while hepatic glycogen content was decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 58 publications
1
15
0
3
Order By: Relevance
“…We found that GDM patients with elevated TG levels in the midterm of pregnancy had higher glucose levels and more severe insulin resistance during both pregnancy and the postpartum period. Free fatty acids (FFAs) potentially derived from elevated TGs might decrease insulin sensitivity, creating a vicious cycle between TG levels and insulin resistance [8,34,35]. Excess FFAs could result in the generation of toxic lipids, including diacylglycerides and ceramides.…”
mentioning
confidence: 99%
“…We found that GDM patients with elevated TG levels in the midterm of pregnancy had higher glucose levels and more severe insulin resistance during both pregnancy and the postpartum period. Free fatty acids (FFAs) potentially derived from elevated TGs might decrease insulin sensitivity, creating a vicious cycle between TG levels and insulin resistance [8,34,35]. Excess FFAs could result in the generation of toxic lipids, including diacylglycerides and ceramides.…”
mentioning
confidence: 99%
“…These disturbances may have occurred through physiological stress, oxidative stress, and other mechanisms (141). These results were confirmed by in vivo studies; for example, malathion induced insulin resistance biomarkers and reduced insulin sensitivity (140). Other studies reported that, in general, OPs increased blood glucose (142)(143)(144) and induced glycogen phosphorylase and phosphoenolpyruvate carboxykinase activity following malathion treatment in rats (145).…”
Section: Parathion and Malathion Induce Metabolic Alterationsmentioning
confidence: 71%
“…In this context, particularly in cell metabolism and metabolic pathways, certain studies reported glucose homeostasis impairment (137) and metabolic disorders, with certain metabolic changes still present for a long time even after discontinuing long-term exposure to malathion (140), which was due to OPs. These disturbances may have occurred through physiological stress, oxidative stress, and other mechanisms (141).…”
Section: Parathion and Malathion Induce Metabolic Alterationsmentioning
confidence: 99%
“…However, reports are mainly based on in vitro and animal models studies on organ toxicity. [38][39][40][41]. Secondly, most of the studies were related with mild toxic OPs like malathion [42,43], whereas extremely toxic OP, for instance, paraoxon or mixtures of Ops, may exhibit different toxicological profiles, although they have a common mechanism of poisoning that is inhibition of AChE [10,11].…”
Section: Discussionmentioning
confidence: 99%